Marketing Strategy for Subsidized Housing: An Analysis of Mega Mutiara Tasik Regency in Tasikmalaya City - Saputra, Budi Mahmud (Community Engagement and Emergence Journal (CEEJ), 2025)
As a subsidized housing developer, Mega Mutiara Tasik Regency must formulate an appropriate marketing strategy to address community needs and strengthen its competitive advantage. This research aims to examine the marketing strategy of Mega Mutiara Tasik Regency by employing the 7P marketing mix framework in conjunction with SWOT analysis. The findings indicate that the strategies implemented encompass providing products with a modern minimalist design, competitive pricing supported by flexible mortgage (KPR) schemes, and promotional activities conducted through digital marketing, housing exhibitions, and property agents. The SWOT analysis further reveals that the recommended strategic orientation corresponds to a Rapid Growth strategy (S > O with a score of 1.40 > 1.35), signifying that internal strengths outweigh external opportunities. The developer may capitalize on existing opportunities by enhancing housing material quality, ensuring product reliability, and intensifying promotional efforts through social media and other digital platforms. The formulation and implementation of such marketing strategies are expected to facilitate the achievement of sales targets in the subsidized housing sector while improving market competitiveness.